Pregnancy outcome and follow-up cardiac outcome in women with aortic valve replacement. (March 2014) - Basude, Snehalata; Trinder, Johanna; Caputo, Massimo; Curtis, Stephanie L
Objectives: To compare the maternal, fetal and cardiac outcomes in women who have undergone aortic valve replacement. Method: Retrospective observational study of all women with aortic valve replacement, who underwent a pregnancy (1998–2012). Maternal-, fetal- and valve-related cardiac outcomes were assessed. Results: Thirty-two pregnancies in 16 women with aortic valve replacement (nine bioprosthetic, six Ross and 17 mechanical) were evaluated. There were no adverse maternal events in the bioprosthetic and Ross groups but three in the mechanical group. Fetal loss rate was highest in the mechanical valve pregnancies (53%). One woman in the bioprosthetic group needed valve re-operation, and one woman in the mechanical valve group died. There was no difference in the change of Vmax over the follow-up between the valves ( p  = 0.25). Conclusions: There was no difference in deterioration between aortic valve replacements during and after pregnancy. The highest risk of maternal and fetal complications occurred in the mechanical valve group.